When social safety nets protect economic growth: the case of Cambodia - Stephanie Levy (London School of Economics and Political Science (LSE), Department of International Development, 2021)
Trade-offs between policies that promote economic growth and redistribute wealth are discussed extensively in the literature, both from a public finance perspective and from a macroeconomic angle. In fact, social safety nets are sometimes perceived by government in developing countries as a non-productive use of scarce public finance. Cambodia is an example of low middle income country that has so far been reluctant to implement a social protection floor for its vulnerable population and those unable to meet their subsistence needs. The Covid-19 pandemic has however changed not only the set of policies that the government has put in place to protect its population living in poverty, dedicating an unprecedented share of its budget to their funding, but it has also modified the role that policy makers aim for these interventions to play. These programmes are now increasingly perceived as a requirement to protect the growth of a country that was for decades the fastest growing economy in the world. This paper analyses the policy changes induced by the pandemic and presents empirical evidence that their economic effects are likely to be large. It then discusses the shift in political paradigm that this could lead to.
Keywords: 330; Social Protection; Economic Growth; Cambodia; Covid-19; Economic Inclusion